(untitled) (Journal of Academic Research, 2022)
This study was carried out to determine the heavy metals concentrations such as Fe, Cu, Mn and Zn to know their effects on the desalination units and other components. The samples were collected from feed water intake of Alkhums desalination plant. The plant was chosen because of its importance in supplying fresh water for potable water and industrial uses. These results differences lead to the corrosion by precipitation on the components of desalination units. Moreover heavy metals concentrations were very high compared to the standard rates of the seawater. The mean concentrations of Cu, Fe ,Zn, and Mn at site 2 were ( 2.36,0.042,0.066 and 0.056 ppm) respectively, and site 4 were ( 2.75,0.048,0.071 and 0.06 ppm) respectively.